The Ability of Bioethanol-Methanol Atractants to Attract Bactrocera spp Populations in Chili Plants (Capsicum annuum L.) - Mewengkang, Ferny Tewuh; Salaki, Christina Leta; Rimbing, Jimmy; Paat, Frangky J. (Jurnal Agroekoteknologi Terapan, 2026)
This study aimed to evaluate the ability of a bioethanol-methanol attractant to attract Bactrocera spp. populations in chili fields in West Tompaso District. The research was conducted from November to December 2025 in chili plantations in Tonsewer Village, West Tompaso District, while insect identification was carried out at the Plant Pest and Disease Laboratory, Faculty of Agriculture, Sam Ratulangi University. A randomized block design was used with five treatments, consisting of bioethanol-methanol ratios of 1:1, 1:2, 1:3, and 1:4, along with synthetic ethanol and synthetic methanol at a 1:1 ratio as a comparator, each replicated five times. Observations were conducted every seven days for five weeks. The results showed that the bioethanol-methanol attractant was able to capture three Bactrocera species, namely B. dorsalis, B. carambolae, and B. musae, with a total of 120 individuals. The dominant species were B. dorsalis with 56 individuals and B. carambolae with 55 individuals, whereas B. musae was represented by only 9 individuals. Treatments P1 and P2 showed the highest attractiveness to Bactrocera spp., while P4 and P5 produced the lowest captures and were not significantly different from each other. Differences in treatment effectiveness were presumably associated with the balance of volatility in the bioethanol-methanol mixture, whereas rainfall fluctuations and the biological condition of the insects in the field also influenced trap catches. These findings indicate that the bioethanol-methanol mixture has potential as an alternative attractant for monitoring Bactrocera spp. in chili cultivation. Keywords : attractant, Bactrocera spp., bioethanol-methanol, chili, population Abstrak. Penelitian ini bertujuan untuk mengevaluasi kemampuan atraktan bioetanol-metanol dalam menarik populasi Bactrocera spp pada pertanaman cabai di Kecamatan Tompaso Barat. Penelitian dilaksanakan selama November hingga Desember 2025 pada pertanaman cabai di Desa Tonsewer, Kecamatan Tompaso Barat, dan identifikasi sampel dilakukan di Laboratorium Hama dan Penyakit Tumbuhan, Fakultas Pertanian, Universitas Sam Ratulangi. Penelitian menggunakan Rancangan Acak Kelompok dengan lima perlakuan, yaitu rasio bioetanol-metanol 1:1, 1:2, 1:3, 1:4, serta etanol sintetik dan metanol sintetik 1:1 sebagai pembanding, dengan lima ulangan. Pengamatan dilakukan setiap tujuh hari selama lima minggu. Hasil penelitian menunjukkan bahwa atraktan bioetanol-metanol mampu menarik tiga spesies Bactrocera, yaitu B. dorsalis, B. carambolae, dan B. musae, dengan total 120 individu. Spesies yang dominan adalah B. dorsalis sebanyak 56 individu dan B. carambolae sebanyak 55 individu, sedangkan B. musae hanya 9 individu. Perlakuan P1 dan P2 menunjukkan daya tarik tertinggi terhadap Bactrocera spp, sedangkan P4 dan P5 memberikan hasil terendah dan tidak berbeda nyata. Perbedaan efektivitas antarperlakuan diduga dipengaruhi oleh keseimbangan volatilitas campuran bioetanol-metanol, sementara fluktuasi curah hujan dan kondisi biologis serangga di lapangan turut memengaruhi jumlah tangkapan. Dengan demikian, campuran bioetanol-metanol berpotensi digunakan sebagai atraktan alternatif untuk monitoring Bactrocera spp pada tanaman cabai. Kata Kunci : atraktan, Bactrocera spp, bioetanol-metanol, cabai, populasi